KARAWITAN TARI WANARA PARISUKA DI OBJEK WISATA GOA KREO KOTA SEMARANG : KAJIAN GARAP GENDHING TARI GARAPAN BARU (Universitas Negeri Semarang, 2017)
Garap music of Wanara Parisuka in Goa Kreo Attraction of Semarang City in the form of collaboration between gendhing-gendhing Java and kentongan music with various rhythmic playing pattern interesting to be studied. The problem discussed is how to garap music Wanara Parisuka Dance. The purpose of this research is to know, explain vocabulary gendhing and garap music of Wanara Parisuka Dance. The research used qualitative descriptive approach. The results show that the vocabulary gendhing used in the dance is in the form lancaran, namely: Lancaran Kotekan and the Wanara Parisuka. The first time was used as a material to support the dance part that was exhibited by the children, while the second was for the material to work on adult dance music. The two lancaran of the pelog nem are presented collaboratively using Javanes gamelan and kentongan devices repeatedly according to the pattern of dance moves in a lancar rhythm. Kendang plays the patterns of the game following the pattern of motion of dance, consisting of nine patterns namely: budalan mangkat, sabetan, joget muter, jogetan menggaruk, dolanan, loncat ulap, lampah tigo, megot, and budalan mulih. The kentongan plays three playing patterns, namely: kentongan 1, kentongan 2, and kentongan 3 with together